(untitled) (The Pakistan Development Review, 2015)
The process of urbanisation has dual impact on the development process of an economy. Initially, it encourages the workers to switch from low productive sector i.e. agriculture to high productive sectors like services and manufacturing [Becker, et al. (1994)]. Subsequently, it generates formidable problems for residents by depriving them of access to essential basic needs [Egziabher (2000)]. It is also observed that the poor try to urbanise faster as compared to the whole population [Ravallion (2007)] and this urbanisation process leads toward the emergence of urban poverty. Urban poverty is distinct from the rural poverty with respect to its incidence, economic, demographic and political aspects. The urban poverty can be controlled by developing the clear understanding of its nature, magnitude and intensity